2016
DOI: 10.1080/19768354.2016.1140676
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-mediated anti-inflammatory effect through NFκB is preserved in the absence of Dexras1

Abstract: View related articlesView Crossmark data Citing articles: 1 View citing articles Glucocorticoid-mediated anti-inflammatory effect through NFκB is preserved in the absence of Dexras1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In order to provide a mechanism by which we can reduce side effects of glucocorticoids, it is also important to investigate whether Dexras1 is involved in anti-inflammatory effects of glucocorticoids. In this regard, our report that glucocorticoid-mediated NF-κB suppression is preserved in the absence of Dexras1 34 might be interesting to note, thus the inhibition of Dexras1 would be a great target for reducing steroid-mediated side effects. Additional future studies should seek to determine the glucocorticoid-mediated effect of adipogenesis in vivo , perhaps by using animals treated with an excess glucocorticoids.…”
Section: Discussionmentioning
confidence: 83%
“…In order to provide a mechanism by which we can reduce side effects of glucocorticoids, it is also important to investigate whether Dexras1 is involved in anti-inflammatory effects of glucocorticoids. In this regard, our report that glucocorticoid-mediated NF-κB suppression is preserved in the absence of Dexras1 34 might be interesting to note, thus the inhibition of Dexras1 would be a great target for reducing steroid-mediated side effects. Additional future studies should seek to determine the glucocorticoid-mediated effect of adipogenesis in vivo , perhaps by using animals treated with an excess glucocorticoids.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies demonstrated that corticosteroids like Dex phosphate contributed to an anti-inflammatory effect through inhibiting the nuclear factor-kappa B (NF-κB) signal pathway. [ 5 , 6 ] However, whether corticosteroids eye drops are proper for infectious keratitis cure remains a controversial topic. [ 7 ] Lu et al proved that dexamethone could inhibit IL-1-induced collagen degradation and decrease stroma scarring.…”
Section: Introductionmentioning
confidence: 99%
“…PPARγ, known as essential modulators, can regulate nuclear factor-κB (NF-κB) activation in anti-inflammation (Yong et al 2016). Several studies have reported that PPARγ can suppress inflammatory expression by direct interaction with NF-κB, p65 and p50 subunits (Ricote & Glass 2007).…”
Section: Introductionmentioning
confidence: 99%